Functional Outcome following Headless Compression Screw Fixation for Hamate Fractures - van Rijckevorsel, Veronique A.J.I.M.; Selles, Caroline A.; van der Vlies, Cornelis H.; Cleffken, Berry I.; Schep, Niels W.L. (Journal of Wrist Surgery, 2020)
Hamate fractures can be treated nonoperatively, with the percutaneous Kirschner wire (K-wire) fixation, or with excision of a fractured hook of the hamate. Screw fixation is less popular owing to the risk of iatrogenic ulnar nerve injury. The aim of this study was to present the functional results of patients with hamate fractures treated with headless compression screws (HCS). The primary outcome was the Michigan Hand Outcome Questionnaire (MHOQ) after at least 4 months of follow-up. Nine patients were included in this retrospective cohort study. A median MHOQ total score of 67% was reported (interquartile range [IQR]: 44–76). No complications were found during follow-up. HCS fixation is a safe alternative to treat hamate fractures with good functional outcome. This is a Level IV study.
Keywords: hamate fracture; osteosynthesis; headless compression screws; functional outcome